A prospective observational study on role of laparoscopy in patients presenting with abdominal trauma in a tertiary care government medical college in Uttar Pradesh - Akash Gupta; Chitrangana Gupta (Asian Journal of Medical Sciences, 2023)
Background: Laparoscopic surgery, also called minimal access surgery or key hole surgery, is a modern surgical technique, in which operations are performed far from their location through small incisions (usually 0.5–1.5 cm). Aims and Objectives: The aim of the study was to study the role of diagnostic laparoscopy (DL) in reassessing solid organ injury, diagnosing occult injuries, and selecting patients for conservative or operative line of management in cases of abdominal trauma with equivocal findings on CT scan And to study the role of therapeutic laparoscopy in a select group of cases where it can follow the initial DL and avoid laparotomy. Materials and Methods: The prospective study source of data will be from patients a presenting with abdominal trauma in the emergency at M.L.B. Medical College Jhansi (Trauma Centre). The duration of study will be from May 2021 till December 2022. We concluded that total study size of 152 patients for the assessment of diagnostic and therapeutic laparoscopy. Results: Among this, 130 (85.53%) were male patients. Females were 22 (14.47%). Most of the abdominal trauma caused by road traffic accidents 116 (76.32%). Other mode of injuries are assault, fall from height, gunshot injuries, and working machine-related injuries. Most commonly involved age groups are young adults between 21 and 30-year age group (42.76%). Most commonly injured organ is the spleen, i.e., 45 cases (30%) followed by liver, i.e., 23 cases (18.63%). Conclusion: In our study, we concluded that laparoscopic surgery can be considered an alternative option over conventional laparotomy.